EAACI guidelines on allergen immunotherapy: prevention of allergy - Halken, Susanne; Pfaar, Oliver (Pediatric allergy and immunology, 2017)
Allergic diseases are common and frequently coexist. Allergen immunotherapy (AIT) is a disease-modifying treatment for IgE-mediated allergic disease with effects beyond cessation of AIT that may include important preventive effects. The European Academy of Allergy and Clinical Immunology (EAACI) has developed a clinical practice guideline to provide evidence-based recommendations for AIT for the prevention of (i) development of allergic comorbidities in those with established allergic diseases, (ii) development of first allergic condition, and (iii) allergic sensitization. This guideline has been developed using the Appraisal of Guidelines for Research & Evaluation (AGREE II) framework, which involved a multidisciplinary expert working group, a systematic review of the underpinning evidence, and external peer-review of draft recommendations. Our key recommendation is that a 3-year course of subcutaneous or sublingual AIT can be recommended for children and adolescents with moderate-to-severe allergic rhinitis (AR) triggered by grass/birch pollen allergy to prevent asthma for up to 2 years post-AIT in addition to its sustained effect on AR symptoms and medication. Some trial data even suggest a preventive effect on asthma symptoms and medication more than 2 years post-AIT. We need more evidence concerning AIT for prevention in individuals with AR triggered by house dust mites or other allergens and for the prevention of allergic sensitization, the first allergic disease, or for the prevention of allergic comorbidities in those with other allergic conditions. Evidence for the preventive potential of AIT as disease-modifying treatment exists but there is an urgent need for more high-quality clinical trials.